Analysis of Mangrove Vegetation in Mesjid Raya Sub-District, Aceh Besar District - Rianda Pratama; Djufri Djufri; Nazar Muhammad; Vivera Ruselli Puspa (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2024)
Mangrove ecosystems, characterized by their unique adaptation to intertidal zones along coastlines and river estuaries, play a crucial role in coastal ecology. This study investigated the composition and diversity of mangrove vegetation in Mesjid Raya District, Aceh Besar Regency. Employing a quantitative approach with purposive sampling, nine plots measuring 10x10 meters were established across three stations with varying physical environmental conditions, totaling 90 plots. Vegetation analysis revealed the presence of nine mangrove species belonging to five families. The Shannon diversity index (Ĥ) indicated a low level of species diversity within the studied mangrove communities.